2015
DOI: 10.1016/j.blre.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Platelet secretion: From haemostasis to wound healing and beyond

Abstract: Upon activation, platelets secrete more than 300 active substances from their intracellular granules. Platelet dense granule components, such as ADP and polyphosphates, contribute to haemostasis and coagulation, but also play a role in cancer metastasis. α-Granules contain multiple cytokines, mitogens, pro- and anti-inflammatory factors and other bioactive molecules that are essential regulators in the complex microenvironment of the growing thrombus but also contribute to a number of disease processes. Our un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
509
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(566 citation statements)
references
References 137 publications
1
509
0
15
Order By: Relevance
“…Despite the importance of dense-granule secretion in platelet function, 24 signaling pathways specifically regulating this process are not well defined. Although a definitive involvement of MAP3Ks remains to be elucidated, the present study showed that MINK1 acts upstream of MEK1/2, MKK3/6, p38, ERK, and Akt, sequentially and specifically regulating dense-granule secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of dense-granule secretion in platelet function, 24 signaling pathways specifically regulating this process are not well defined. Although a definitive involvement of MAP3Ks remains to be elucidated, the present study showed that MINK1 acts upstream of MEK1/2, MKK3/6, p38, ERK, and Akt, sequentially and specifically regulating dense-granule secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Gracias a modelos animales, ahora se sabe que la disminución de la actividad de la eNOS es parte fundamental de la fisiopatología de la hipertensión portal (18,19). Las plaquetas, además de servir como elemento celular en el tapón hemostático, poseen gránulos intracelulares con elementos capaces de modificar los procesos inflamatorios e inmunológicos dentro del hígado (10). Los gránulos α contienen factores de crecimiento cuya diana son las vías Akt (fosfatidilinositol-3-kinasa/AKT [PI3K-Akt]) y extracellular signal-regulated kinase (ERK) 1/2, ambas trascendentales para el hepatocito (20) al grado que recientes investigaciones sugieren que la transfusión de plaquetas puede mejorar la regeneración hepática (20,21).…”
Section: Alteraciones En La Hemostasia Primariaunclassified
“…Serotonin is not the only molecule secreted by platelets; the other include ADP, ATP, GDP, pyrophosphate, magnesium and calcium [14]. Platelets acquire serotonin from the plasma by means of the cell membrane serotonin uptake mechanism [15], and store the serotonin in dense granules [14].…”
Section: The Anti-serotonin Approachmentioning
confidence: 99%